PENGARUH KOMITE SEKOLAH DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP PENINGKATAN MUTU PENDIDIKAN - Ningsih, Kartini Dewi; Harapan, Edi; Destiniar, Destiniar (Graduate Program Magister Manajemen Pendidikan, 2021)
This study aimed at determining whether there is an influence of school committees and principals' leadership on improving the quality of education. This research was conducted at Sukarami District Palembang Junior High School. This research is quantitative, while the method used is simple regression and multiple regression. The sample in this study were 148 committee members and teachers. Data were collected using questionnaire. The results of the study concluded that (1) there was a significant influence on the school committee on improving the quality of education; (2) there was a significant influence of the principal’s leadership on improving the quality of education; and (3) there was a significant influence jointly the school committee and the principal's leadership on improving the quality of education.